Induction of Heme Oxygenase-1 Modifies the Systemic Immunity and Reduces Atherosclerotic Lesion Development in ApoE Deficient Mice - Yao, Leyi; Hao, Yali; Wen, Guanmei; Xiao, Qingzhong; Wu, Penglong; Wang, Jinheng; Liu, Jinbao (Frontiers in Pharmacology, 2022)
Heme oxygenase-1 (HO-1) has been reported to protect against oxidation and inflammation in atherosclerosis. It remains unclear how the immune system participates in the cytoprotective function of HO-1 in the context of atherosclerosis. In this study, we attempted to investigate the potential effect of a HO-1 inducer, hemin, and a HO-1 inhibitor, Tin-protoporphyrin IX (SnPP), on the progression of atherosclerosis in ApoE deficient mice. Using mass cytometry, 15 immune cell populations and 29 T cell sub-clusters in spleen and peripheral blood were thoroughly analyzed after hemin or SnPP treatment. SnPP elevated risk factors of atherosclerosis, whereas hemin reduced them. In-depth analysis showed that hemin significantly modified the immune system in both spleen and peripheral blood. Hemin increased dendritic (DC) and myeloid-derived suppressor cells (MDSCs), but decreased natural killer (NK) cells. An opposite effect was observed with SnPP treatment in terms of NK cells. NK cells and MDSCs were positively and negatively correlated with total cholesterol and low-density lipoprotein, respectively. Moreover, the T cell profiles were significantly reshaped by hemin, whereas only minor changes were observed with SnPP. Several hemin-modulated T cell clusters associated with atherosclerosis were also identified. In summary, we have unraveled an important regulatory role for HO-1 pathway in immune cell regulation and atherosclerosis. Our finding suggests that modulating HO-1 signaling represents a potential therapeutic strategy against atherosclerosis.